Synthesis and Antimicrobial Evaluation of 6-Alkylamino-N-phenylpyrazine-2-carboxamides - Servusová, Barbora; Paterová, Pavla; Garaj, Vladimír; Mandíková, Jana; Kuneš, Jiří; Naesens, Lieve; Jílek, Petr; Doležal, Martin; Zitko, Jan (Chemical biology & drug design, 2015)
This work presents synthesis and antimicrobial evaluation of nineteen 6-alkylamino-N-phenylpyrazine-2-carboxamides. Antimycobacterial activity was determined against Mycobacterium tuberculosis H37Rv, M. kansasii and two strains of M. avium. Generally, the antimycobacterial activity increased with prolongation of simple alkyl chain and culminated in compounds with heptylamino substitution (3e, 4e) with MIC = 5-10 μm against M. tuberculosis H37Rv. On the contrary, derivatives with modified alkyl chain (containing e.g. terminal methoxy or hydroxy group) as well as phenylalkylamino derivatives were mainly inactive. The most active compounds (with hexyl to octylamino substitution) were evaluated for their in vitro activity against drug-resistant strains of M. tuberculosis and possessed activity comparable to that of the reference drug isoniazid. None of the tested compounds were active against M. avium. Some derivatives exhibited activity against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (best MIC = 7.8 μm), while Gram-negative strains as well as tested fungal strains were completely unsusceptible. Active compounds were tested for in vitro toxicity on various cell lines and in most cases were non-toxic up to 100 μm.
Keywords: Animals; Antifungal Agents; Mycobacterium tuberculosis; buněčné linie; antituberkulotika; mikrobiální testy citlivosti; techniky syntetické chemie; simulace molekulového dockingu; Structure-Activity Relationship; lidé; antiinfekční látky; Anti-Infective Agents; Chemistry Techniques, Synthetic; Drug Evaluation, Preclinical; methicilin rezistentní Staphylococcus aureus; Cell Line; Microbial Sensitivity Tests; preklinické hodnocení léčiv; vztahy mezi strukturou a aktivitou; Antitubercular Agents; zvířata; antifungální látky; Molecular Docking Simulation; Methicillin-Resistant Staphylococcus aureus; Humans